The Effect of Service Quality and Financial Literacy on Customers' Interest in Investing in Gold : (Case Study at PT Pegadaian (Persero) Kotamobagu Branch) - Fidya Dwi Fransiskan S. Yasin; Hartati Tuli; Titi Umi Kalsum Hulopi (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of service quality and financial literacy on customer interest in investing in gold at PT Pegadaian (Persero), Kotamobagu Branch. A quantitative research method was used, with primary data collected through a questionnaire distributed to PT Pegadaian (Persero) customers. The sample consisted of 106 respondents. Data analysis used multiple linear regression with the help of SPSS 26. The results of the study show that the quality of service has a positive and significant effect on customers' interest in investing in gold. Financial literacy also has a positive and significant effect on customers' interest in investing in gold. Together, the quality of service and financial literacy have a significant effect on the interest of customers to invest in gold at PT Pegadaian (Persero) Kotamobagu Branch. The R-square value obtained was 0.687 or 68.7%, this shows a strong relationship between independent variables and dependent variables in this study, while the remaining 37.3% were influenced by other factors.